Optimizing investment and transportation decisions for the European natural gas supply chain - Olmez Turan, Merve; Flamand, Tulay (Applied energy, 2023)
We address the European natural gas supply chain with several tiers, including producers, mid-streamers, and consumers, where natural gas and Liquefied Natural Gas (LNG) could be traded via long-term contracts or spot markets. This network problem is formulated as a non-linear mixed-integer programming model which provides the optimal production and export decisions of producers, import and storage decisions of mid-streamers, and infrastructure investment decisions of European Union (EU) countries with respect to new pipelines and LNG regasification terminals that maximize the total social welfare in the EU natural gas market over a five-year horizon. We conduct several case studies to examine this network under different conditions. We first compare the actual and optimal decisions to provide insights. Then, we examine the effect of infrastructure decisions on social welfare. Our results reveal that new infrastructure investments increase the total social welfare by nearly three billion. In addition, we examine its sensitivity to the exclusion of Russian gas supply from the market with and without the infrastructure decisions. Results suggest that if Russian gas supply is excluded from the market, then the social welfare and cumulative natural gas consumption of 26 EU countries decrease by 10% and 15%, respectively and that considering infrastructure investments on LNG terminals and pipelines would reduce supply risk of consumer countries. •This paper addresses the European natural gas supply chain with several tiers.•An optimization model is proposed to obtain investment and transportation decisions.•Optimal decisions increase the social welfare by nearly three billion.•Excluding Russia decreases the social welfare by 10% for the next five years.